Method of Parents in the Development of Child Prayers Attention Deficit Hyperactivity Disorder (ADHD) (Case Study of ADHD Children in Kulam Kemukiman Syamtarail Village, North Aceh) - Muhajir; Zahrul Mubarrak; Amiruddin; Khaidir; Fazil Saputra; Muhammad Ridha (Britain International for Academic Research (BIAR) Publisher, 2019)
Concentration disorders accompanied by hyperactivity in children with ADHD are conditions that show symptoms of lack concentration, hyperactivity and impulsiveness that causes an imbalance of most of their life activities. This makes parents have difficulty in providing prayer guidance to children who have ADHD. Starting from this problem, the researcher tries to make a scientific about Parents' Method in the Development of Child Prayers Attention Deficit Hyperactivity Disorder (ADHD) (Case Study of ADHD Children in Kulam Kemukiman Syamtarail Village, North Aceh).